PENINGKATAAN KAPASITAS PEMBUDIDAYA IKAN NILA KERAMBA MELALUI MANAJEMEN LINGKUNGAN DAN PENGUATAN ORIENTASI PASAR DI DESA AWANG BANGKAL BARAT - Yulius Kisworo i22026; Rozzana Erziaty (Fakultas Pertanian UVAYA Banjarmasin, 2026)
This community service program aimed to enhance the capacity of tilapia cage farmers through strengthening their understanding of environmental management and market orientation in Awang Bangkal Barat Village, Banjar Regency. The program employed an educational socialization method with a participatory approach involving 10 cage fish farmers. The materials presented included water quality management, water pollution control, efficient feed utilization, market orientation, and strategies to improve the competitiveness of aquaculture products. Evaluation was conducted using questionnaires and analyzed through descriptive statistics in the form of frequency distributions and percentages based on a fivepoint Likert scale. The results showed that the participants responded positively and actively participated in discussions and question andanswer sessions. The level of understanding after the activity showed that 6 participants (60%) were categorized as understanding, 2 participants (20%) as highly understanding, and 2 participants (20%) as moderately understanding. No participants were categorized as less understanding or not understanding. These findings indicated that the socialization activity effectively improved farmers’ understanding of environmental management practices and fish marketing strategies. The activity was recommended for further implementation through continuous assistance and broader participant involvement to support the sustainability of tilapia cage farming.